The Role of Digital & Health Literacy Development In Mundung Satu Community North Sulawesi - Ivonne Angelic Umboh; Christian Apolinaris Lombogia; Patricia Giovana Junita Petrus; Raphael Yosaphat Sengkey; Anastasia Sintia Lomonge; Getsemani Jhosfreed Gledy Lebe (International Journal Of Community Service, 2024)
This Community Service activity was carried out in Mundung Satu Village, East Tombatu District, Southeast Minahasa Regency, North Sulawesi Province, which was carried out for one day and was scheduled for November 18 2022. Activities in community service included digital literacy education and public health. Digital literacy activities include social media literacy and online loan literacy. Health literacy is a physical examination measuring the patient's vital signs and simple laboratory tests. First, registration is carried out, then an analysis of vital signs (TTV), consultation with a doctor, simple laboratory tests including blood sugar, cholesterol, uric acid and treatment according to the results of the examination, as well as education related to Diabetes, Cholesterol, Gout Arthritis and Hypertension. This activity was carried out while paying attention to health protocols by wearing a mask, washing hands and keeping a distance during the examination from 08.00 to 13.00 WITA. Community Service Activities aims to provide digital and health literacy to the community so that people become literate in terms of social media, the internet and online loans. Whereas in health, literacy is to increase awareness of healthy living to avoid various degenerative diseases, including Diabetes, Hypercholesterolemia, Gout Arthritis and Hypertension. Besides this, free medical treatment is also provided to the community.